ERGO1 - physical evaluation and training for wheelchair users - Augusto Albino Vieira, S.; Amaral de Araújo, C.; Soares dos Santos, S. (Proceedings of the 2nd International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2014)
According to the literature, there's a lack of methods, procedures and equipments for proper physical assessment. Physical tests applied to persons with disabilities are questionable due to their lack of adaptation to the motor gesture executed in these equipments, which are not the same executed in real wheelchair propulsion. Within this, was designed and built at the Habilitation/Rehabilitation Center in Paralympic Sports/UFU the second version of a wheelchair ergometer prototype that allows physical evaluation, being faithful to the specificity of movements. The equipment has several electronic systems controlled by computer such as electromagnetic resistance system, load cell, torquemeter, dedicated circuits and acquisition system. Preliminary results indicate that the evolution became more practical for the evaluator and comfortable for the user. The addition of flywheels and new calibration method proved its efficiency by improving the signal acquired. New evaluation procedures for physical capacity look promising.